Review Article How Can Occupational Medicine Research Ensure it Adheres to Research and Publication Ethics? - Aditya Nugraha Artar (ILUNI MKK FKUI and PRODI MKK FKUI, 2025)
Background: Occupational health research plays a vital role in protecting worker health, preventing work-related diseases, and promoting a safe workplace. However, its success depends not only on the quality of scientific findings but also on adherence to research and publication ethics.Methods:This study presents a narrative literature review analyzing ethical principles throughout the stages of occupational health research. Sources reviewed include international ethical guidelines, scientific journal policies, and national regulations on public health research ethics.Results: Findings highlight that ethical approval by independent committees, continuous and substantive informed consent, and strict data confidentiality are key elements in ensuring research integrity. Additionally, managing conflicts of interest, responsible authorship practices, and preventing plagiarism, fabrication, and falsification of data are critical indicators of ethical compliance. The collaborative roles of researchers, institutions, funders, and government are essential in building an ethical research ecosystem.Conclusion: The consistent and comprehensive application of ethical principles in occupational health research leads to credible and policy-relevant scientific evidence. Cross-sector efforts are required to ensure ethical compliance and sustainability in the field.